2022
DOI: 10.3390/ma15072587
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Properties of Porous Geopolymers Based on TPP Ash and Slag Waste by Adjusting Their Chemical Composition

Abstract: The possibility of improving the properties of porous geopolymer materials based on ash and slag waste from thermal power plants by adjusting their chemical composition is considered. An X-ray phase analysis of ash and slag wastes was carried out, the geopolymers’ precursor compositions were calculated, and additives to correct their chemical composition were selected. The samples were synthesized and their physical and mechanical properties (density, porosity, compressive strength, thermal conductivity) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…However, in the study by Xinyu Li [57], the minimum density For alkaline activation of aluminosilicate materials, a mixture of waterglass (sodium hydrosilicate mNa 2 O•nSiO 2 •pH 2 O, silicate modulus = 2, water content 53 wt.%, LONTREK, Moscow, Russia) was used as an activating agent along with a solution of NaOH. As previous studies by the authors have shown [64,65], the optimal molar concentration of NaOH solution ranges from 8 to 12 M, as further increase reduces the compressive strength of foamed geopolymer materials. This conclusion is also supported by research from other authors [66,67].…”
Section: Characterization Of the Raw Materialsmentioning
confidence: 80%
See 1 more Smart Citation
“…However, in the study by Xinyu Li [57], the minimum density For alkaline activation of aluminosilicate materials, a mixture of waterglass (sodium hydrosilicate mNa 2 O•nSiO 2 •pH 2 O, silicate modulus = 2, water content 53 wt.%, LONTREK, Moscow, Russia) was used as an activating agent along with a solution of NaOH. As previous studies by the authors have shown [64,65], the optimal molar concentration of NaOH solution ranges from 8 to 12 M, as further increase reduces the compressive strength of foamed geopolymer materials. This conclusion is also supported by research from other authors [66,67].…”
Section: Characterization Of the Raw Materialsmentioning
confidence: 80%
“…The thermal conductivity of the geopolymers was measured using a thermal conductivity meter (ITP-MG4"100/Zond", SKB StroyPribor, Chelyabinsk, Russia) employing the stationary heat flow method. The temperature of the hot and cold faces was set at 34 where λ-effective thermal conductivity, W/m•K; H-sample height, cm; q-density of stationary heat flux passing through the measured sample, W/m 2 ; T H -temperature of the sample's hot face, K; T C -temperature of the sample's cold face, K. The methodology and equipment necessary for determining the linear dimensions as well as certain physical-mechanical properties (volume, density, porosity, compressive strength) of porous geopolymers were described in the authors' previous research [26,64]. Each recorded test value is the medium of 4 measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Yatsenko et al [6] provided an article entitled "Improving the Properties of Porous Geopolymers Based on TPP Ash and Slag Waste by Adjusting Their Chemical Composition". The possibility of improving the properties of porous geopolymer materials based on ash and slag waste from thermal power plants by adjusting their chemical composition is considered.…”
Section: Contributionsmentioning
confidence: 99%
“…Several countries have already identified limited applications for these waste materials, including their use in ceramic production and cement manufacturing, as concrete additives and ameliorants, for road and dam construction, etc. [1][2][3]. In terms of chemical composition, coal combustion wastes (CCWs) exhibit a complex matrix, containing oxides of silicon, aluminum, iron, magnesium, and others.…”
Section: Introductionmentioning
confidence: 99%